Efficacy of semi-occluded vocal tract exercises in essential tremor: a case study - Arias, Tatiana Romero; Betancort Montesinos, Moisés; Hernández Kauffman, Cristina; Pérez del Olmo, Adrián (Revista de Investigación en Logopedia, 2023)
Essential tremor is a neurological disease that manifests itself with movement disorders, with the person suffering from it experiencing tremors that they cannot control. In addition to tremors in the hands, they also manifest tremors in the jaw and larynx, leaving mainly the voice of these patients affected. On the other hand, semi-enclosed vocal tract exercises have been shown to cause beneficial changes in the vibratory pattern of vocal folds. That is why the clinical case of a 61-year-old woman diagnosed with essential tremor is presented in order to verify the effectiveness of semi-enclosed vocal tract exercises in patients with this disease. The results after speech therapy intervention showed a decrease in the Hertz of the voice formers, an improvement of continuous phonation and improvement of prosody. Therefore, it is concluded that the use of semi-enclosed vocal tract exercises could be beneficial in patients with essential tremor.